Research Capacity and Training Needs for Cancer in Conflict-Affected MENA Countries. Issue 1 (6th November 2020) - Abdul-Sater, Zahi; Kobeissi, Elsa; Menassa, Marilyne; Telvizian, Talar; Mukherji, Deborah
Background: The global cancer burden is disproportionately greater in low- and middle-income countries, including those affected by conflict in the Middle East and North Africa (MENA) region. Contributing factors include inadequate control of risk factors plus limited surveillance and treatment options. Weak healthcare infrastructure may be further compounded by the conflict prevalent in multiple MENA countries. Improved cancer surveillance, research, and capacity strengthening are essential for implementing cancer control plans in the MENA region, requisite for reducing the disproportionate cancer burden. Aims: This article aims to understand the barriers to cancer research and training in conflict-affected MENA countries, and to identify opportunities for developing capacities for reliable cancer research strategies. Methods: This study employs a mixed-method approach utilizing an online questionnaire with open and close ended questions targeting oncologists and cancer researchers in conflict-affected MENA countries. For open-ended questions, we performed a qualitative content analysis to identify thematic barriers. Results: Forty-eight respondents, mostly Medical and Radiation Oncologists, completed the questionnaire. The most significant training needs were conducting clinical, basic, and qualitative cancer research. The most prominent barriers identified were insufficient training in data analysis and research design (77% and 75% of respondents, respectively) and insufficient institutional and government funding (94% and 85%, respectively). For the qualitative data, we organized the barriers into six themes, the most common was the lack of research infrastructure (28%). Conclusions: Despite an escalating cancer burden, conflict-affected MENA countries are lagging in knowledge production and implementation of evidence-based cancer research. Novel modes of knowledge transmission and collaboration across geographical and political boundaries are sorely needed. Based on our study, we recommend developing innovative and accessible training opportunities focusing on developing basic, clinical, and qualitative research skills. Research capacity-strengthening initiatives should encourage the investigation of context-specific research questions with the potential to make a meaningful impact on cancer control in the region.